2009
DOI: 10.1111/j.1095-8649.2009.02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Intercalibration of hydroacoustic and mark–recapture methods for assessing the spawning population size of a threatened fish species

Abstract: Hydroacoustic counting and a three-year mark-recapture study with passive integrated transponders (PIT tags) were used to estimate the size of a spawning population of nase Chondrostoma nasus, a threatened potamodromous cyprinid that undertakes annual spawning migrations into a tributary of the Danube River. In 2005, the estimates of the size of the spawning population from the hydroacoustic counts (N = 2234, 95% CL 1929-2538) and from the Jolly-Seber model (N = 1198, 95% CL 461-5842) corresponded well. Estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The winter use of sheltered areas (e.g. deep water areas, pools, side channnels) has been observed for cyprinids (Heermann and Borderding 2006;Irmler et al 2008;Rakowitz et al 2009), salmonids (Cunjak and Power 1986;Swales et al 1986) and a variety of other species (e.g. Esox lucius Kobler et al 2008b).…”
Section: Toleration Survival Strategiesmentioning
confidence: 99%
“…The winter use of sheltered areas (e.g. deep water areas, pools, side channnels) has been observed for cyprinids (Heermann and Borderding 2006;Irmler et al 2008;Rakowitz et al 2009), salmonids (Cunjak and Power 1986;Swales et al 1986) and a variety of other species (e.g. Esox lucius Kobler et al 2008b).…”
Section: Toleration Survival Strategiesmentioning
confidence: 99%
“…They have been used to mark a variety of fish species for monitoring population characteristics such as growth, mortality, abundance, and movement (e.g., Quinn and Peterson 1996;Hutchings and Gerber 2002;DeHaan et al 2007;Al-Chokhachy and Budy 2008). When PIT tags are used to study fish population characteristics, the retention rates are assumed to be high but often are not estimated (e.g., Marsh et al 2005;Rakowitz et al 2009;Zelasko et al 2010).…”
mentioning
confidence: 99%
“…Antenna arrays detected ~1.7-3.2× (humpback chub), ~10-12× (flannelmouth sucker) and 1.2-2× (bluehead sucker) more individuals than were physically captured (Figure 4). Other studies have also reported improved inference with array detections or hydroacoustics compared to physical captures (Dudgeon et al, 2015;Dzul et al, 2022;Fraser et al, 2017;Rakowitz et al, 2009), demonstrating how in situ detection methods can greatly improve detection probabilities.…”
Section: Discussionmentioning
confidence: 94%